Spontaneously acquired unilateral macrotia in an adult: Case report - Cevizci, Raşit; Düzlü, Mehmet; Üstün Bezgin, Selin; Göksu, Nebil (Logos Medical Publishing, 2015)
Macrotia is one of the rare congenital external ear deformities. This deformity occurs when the measurements of the ear exceeds the standard values. However, enlargement of the ear may occur secondary to other causes and have clinical implications similar to true macrotia. In this report, we present an adult who had previously unilateral, slight auricular asymmetry on his left ear. His left ear enlarged spontaneously within the last four years without genetic, dermatological and rheumatological pathologies. We recommend considering other possibilities in the differential diagnosis and making comprehensive research before surgical intervention to the deformity.

Makrotia ender görülen konjenital dış kulak deformitelerinden biridir. Bu deformite dış kulağın standart boyutlarının artması ile oluşur. Ancak dış kulakta başka nedenlerle de büyüme olabilir ve gerçek makrotia gibi klinik olabilir. Bu raporda, daha önce sol kulağında tek taraflı, hafif dış kulak asimetrisi olan, son dört yıl içinde spontane olarak sol kulağı büyüyen, genetik dermatolojik ve romatolojik patolojisi bulunmayan yetişkin hasta sunulmaktadır. Deformiteye cerrahi müdahale öncesi ayırıcı tanıdaki diğer olasılıkların düşünülmesi ve kapsamlı bir araştırma yapılmasını önermekteyiz.
Yetişkinde kendiliğinden edinilen tek taraflı makrotia: Olgu sunumu
Keywords: Deformity; External Ear; Macrotia